2010
DOI: 10.1002/eji.200940115
|View full text |Cite
|
Sign up to set email alerts
|

Human mucosal leishmaniasis: Neutrophils infiltrate areas of tissue damage that express high levels of Th17‐related cytokines

Abstract: Mucosal leishmaniasis (ML) is characterised by severe tissue destruction. Herein, we evaluated the involvement of the IL-17-type response in the inflammatory infiltrate of biopsy specimens from 17 ML patients. IL-17 and IL-17-inducing cytokines (IL-1b, IL-23, IL-6 and TGF-b) were detected by immunohistochemistry in ML patients. IL-17 1 cells exhibited CD4 1 , CD8 1 or CD14 1 phenotypes, and numerous IL-17 1 cells co-expressed the CC chemokine receptor 6 (CCR6). Neutrophils, a hallmark of Th17-mediated inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
119
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(131 citation statements)
references
References 20 publications
7
119
2
3
Order By: Relevance
“…The latter subtype, initially related to autoimmune disorders and allergen-specific responses, is being studied in Leishmania infections (Pitta and others, 2009;Bacellar and others, 2009;Boaventura and others, 2010). Interestingly, our results seem to confirm such reciprocity, once RORC (the human orthologue of RORγt), needed for Th17 activation, was found to be down-regulated in patients.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The latter subtype, initially related to autoimmune disorders and allergen-specific responses, is being studied in Leishmania infections (Pitta and others, 2009;Bacellar and others, 2009;Boaventura and others, 2010). Interestingly, our results seem to confirm such reciprocity, once RORC (the human orthologue of RORγt), needed for Th17 activation, was found to be down-regulated in patients.…”
Section: Resultssupporting
confidence: 85%
“…Herein, the expression of the cytokine in response to AgIns was slightly up-regulated in patients, without statistical difference in relation to the control. This may be due the presence of IL-10 in the microenvironment, which is capable of impairing IL-17 expression (Boaventura and others, 2010). Previous study of our laboratory verified secreted levels IL-17 in PBMC from ATL patients stimulated by both antigens, but at the same time, IL-10 was produced ( AgSol.…”
Section: Resultsmentioning
confidence: 93%
“…Bacellar et al [40] observed that IL-17 is produced during infection with L. braziliensis and lymphocytes obtained from patients with MCL and CL yielded higher concentrations of IL-17 compared to lymphocytes obtained from uninfected individuals. The presence of T H 17 cells in lesions of CL/MCL was associated with neutrophils and tissue destruction [40, 42]. Our data point to higher levels of T H 17 in the sera of patients infected with L. guyanensis when compared to the other two species identified ( L .…”
Section: Discussionmentioning
confidence: 60%
“…In contrast, IL-17 promoted the progression of cutaneous leishmaniasis in susceptible mice infected with L. major (24), whereas in IL-10-deficient mice infected with L. major, IL-17 was responsible for increased Th1 cell-mediated pathology (25). In humans, a negative association with parasite-induced IL-17 production by PBMCs from patients with cutaneous leishmaniasis and muco-cutaneous leishmaniasis infected with L. braziliensis has been reported (26,27). Thus, these findings indicate subtle and complex roles for IL-17 in leishmaniasis that depends on the parasite species and/or sites of disease and immune cell activation.…”
mentioning
confidence: 99%